(untitled) (CIPEEX, 2025)
Introduction: The popularity of electronic cigarettes among adolescents is extensive and concerning due to the increasing health risks associated with their early and excessive use. Health education about respiratory physiology and the risks of smoking is crucial. This report describes a workshop conducted by second-year medical students in October 2023 for high school students in Goiás. Objectives: To report an extension project focused on respiratory physiology and raising awareness about the damages caused by smoking. Methodology: The project involved 883 high school students from a state school. Activities included contests, interactive lung models, and lectures. The action was divided into three parts: A pre-test to assess prior knowledge, where about 80% of students showed a lack of information. Interactive classes by medical students using mini lung models to explain pathological and non-pathological physiology, addressing myths about electronic cigarettes. A contest with 20 questions to evaluate knowledge acquisition, showing improved understanding. Results: Students significantly increased their knowledge, as evidenced by their correct answers to all contest questions. Conclusions or Recommendations: The extension activity enriched medical students and educated young students about respiratory physiology and electronic cigarette risks. It highlights the importance of continuing health education initiatives to raise awareness and change habits, especially among youth.